Inaction Traps in Consumer Response to Product Malfunctions. (April 2020) - Brigden, Neil; Häubl, Gerald
The authors develop and test a theory of consumer inaction traps in the domain of decisions to either address or endure product malfunctions. According to this theory, the magnitude of product malfunctions can have a paradoxical effect on consumption experience. In particular, the less severe a product malfunction is, the more inclined consumers are to defer the initial decision about whether to take corrective action. Subsequent opportunities for corrective action are devalued relative to previously forgone ones. This dynamic tends to trap consumers in a state of inaction, resulting in their enduring smaller malfunctions longer than larger ones. A consequence of these inaction traps is that minor product malfunctions may result in less enjoyable overall consumption experiences than more severe defects. Evidence from eight experiments and a survey provides support for this theorizing by demonstrating the inaction-trap phenomenon, examining its downstream consequences, shedding light on the psychological dynamics of inaction, and identifying boundary conditions that suggest interventions for counteracting consumers' vulnerability to suffering disproportionately from relatively minor product malfunctions.